Factors Influencing Customer Performance (Case study on tokopedia.com) - Stefany Lutan; Innocentius Bernarto (Universitas Pelita Harapan, 2024)
This research aims to test the influence of variables 1) AI assimilation with organizational and customer agility; 2) AI assimilation with customer relationship quality; 3) AI assimilation with customer experience; 4) Organization and customer agility with customer relationship quality; 5) Organization and customer agility with customer experience; 6) Customer experience with customer relationship quality; 7) Customer relationship quality with customer performance for Tokopedia customers in Jakarta, Bogor, Depok, Tangerang and Bekasi. This research uses a quantitative type of research with data collection tools in the form of questionnaires measured using a Likert scale. The data analysis method was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS version 4 software. Based on the results of data analysis, it shows that there is a significant correlation between AI assimilation and organizational and customer agility, AI assimilation with customer experience, organization and customer agility with customer relationship quality, organization and customer agility with customer experience, customer experience with customer relationship quality, and customer relationship quality with customer performance. And there is no correlation between AI assimilation and customer relationship quality.